2014
DOI: 10.1002/pds.3696
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic decrease in fluoroquinolones in the pediatric population in Korea

Abstract: Korean regulatory actions regarding fluoroquinolones had an effect of reducing use in pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
(9 reference statements)
1
13
0
Order By: Relevance
“…The number of antibiotic prescriptions per 1000 paediatric outpatients was 8984 in 2011, similar to results from the Korean paediatric sample data 13. This greatly exceeds the number in the USA (592 prescriptions) and the UK (537 prescriptions) 29 30.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The number of antibiotic prescriptions per 1000 paediatric outpatients was 8984 in 2011, similar to results from the Korean paediatric sample data 13. This greatly exceeds the number in the USA (592 prescriptions) and the UK (537 prescriptions) 29 30.…”
Section: Discussionsupporting
confidence: 74%
“…Even though the use of broad-spectrum antibiotics might be a cause of treatment failure in AOM, over 50% of antibiotic prescription is amoxicillin/clavulanate in Korea 28 38 39. Quinolone use in Korean paediatrics is in the acceptable range as the result of a nationwide computerised drug utilisation review 13. Considering the relatively high adherence rates for antibiotic prescription to the national clinical guidelines, it is necessary to develop country-specific APQIs and educate practitioners to improve the quality of their antibiotic selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics were the drugs most commonly associated with adverse drug reactions in the pediatric population . Prior research also showed a 94.55% relative reduction in the use of fluoroquinolones in the pediatric population in Korea after the 2009 regulatory action . A recent study in Korea also indicated that the government announcement of drug contraindications immediately reduced the number of prescriptions of age‐contraindicated antibiotics per million prescriptions: by 841 for ciprofloxacin, 1,089 for levofloxacin, and 3,058 for ofloxacin .…”
Section: Discussionmentioning
confidence: 38%
“…Although one study has assessed FQ use in Korean pediatric patients, it used patient sample data and short study period of two years, and thus limited in evaluating the overall, sustained impact of the nationwide intervention [30]. Thus, the aims of our study were 1) to quantify the national pediatric use of fluoroquinolones and 2) to evaluate the sustained as well as immediate effect of nationwide implementation of age restriction on fluoroquinolone use by analyzing the changing rates and patterns of prescription over 9 years.…”
Section: Introductionmentioning
confidence: 99%